2016
DOI: 10.1371/journal.pone.0158806
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Exposure and Sensorineural Hearing Loss in Preterm Infants

Abstract: ObjectiveTo evaluate the impact of gentamicin exposure on sensorineural hearing loss (SNHL) in very low birth weight (VLBW) infants.MethodsExposure to gentamicin was determined in infants born between 1993 and 2010 at a gestational age < 32 weeks and/or with a birthweight < 1500 g, who presented with SNHL during the first 5 years of life. For each case, we selected two controls matched for gender, gestational age, birthweight, and year of birth.ResultsWe identified 25 infants affected by SNHL, leading to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
1
25
3
Order By: Relevance
“…The etiology of sensori-neuronal hearing loss in preterm infants is multifactorial including genetic, infectious (CMV infection) and drug related toxicity (Aminoglycosides) [18,19]. Our study did not reveal specific neuronal hearing loss in 6/7 of the infants studied, despite CSF vancomycin concentration > 40mg/L.…”
Section: Discussioncontrasting
confidence: 59%
“…The etiology of sensori-neuronal hearing loss in preterm infants is multifactorial including genetic, infectious (CMV infection) and drug related toxicity (Aminoglycosides) [18,19]. Our study did not reveal specific neuronal hearing loss in 6/7 of the infants studied, despite CSF vancomycin concentration > 40mg/L.…”
Section: Discussioncontrasting
confidence: 59%
“…Since the first hours of infection are crucial, the administration of antibiotics within 1 h of the identification of sepsis is recommended (60). Therapeutic drug monitoring is recommended for longer courses to evaluate the necessity of adjusting dosing interval on any individual basis (61). Considering that trough gentamicin TDM is cumbersome in neonates and that steady-state definition in neonates is not applicable, a Bayesianbased TDM approach allowing opportunistic TDM at the time of routine blood tests based on one concentration measurement would present numerous advantages (19).…”
Section: Discussionmentioning
confidence: 99%
“…Two risk factors were examined in isolation due to their high frequency of occurrence and known association or equivocal association with hearing loss. One of these factors was treatment with ototoxic medications due to the incongruous findings between hearing loss and ototoxic medications in previous studies (e.g., no association found by Hess et al, 1998, andSetiabudy et al, 2013; association found by Bielecki, Horbulewicz, & Wolan, 2011;Fuchs et al, 2016;Robertson, Tyebkhan, Peliowski, Etches, & Cheung, 2006;Zimmerman & Lahav, 2013) and the high number of babies who received ototoxic medications in the study population. In this study, treatment with ototoxic medications (when combined with other risk factors) was the most prevalent risk factor, and 3.9% of all hearing loss was associated with their use.…”
Section: Risk Factors In Isolationmentioning
confidence: 94%